Sustaining the External Debt of Post-Armed Conflict Countries Reality and Challenges "The Lebanese Case" - Alokab, Yaser Mohammad Ead (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aimed at studying the proposed legal and financial mechanisms to solve the financial crisis that Lebanon is witnessing, while maintaining the economic, financial and monetary strength of the Lebanese state, by relying on the descriptive analytical approach that fits with the nature of the research by collecting data and information on the Lebanese public debt, its sustainability, and its impact on The Lebanese economic and social realities, leading to the most prominent results represented in the countries emerging from armed conflicts asking to contribute to their development and reconstruction, which leads to these countries falling into the trap of indebtedness and financial and political crises. Similar to what happened in the Lebanese case under study, thus staying in the same cycle through the continuity of loan requests and then imposing new extremely difficult conditions aimed at putting pressure on the “debtor” state. Therefore, work must be done to present an integrated recovery plan for the Lebanese economy that works to transform it from a rentier economy into a productive economy, and to work to reduce interest rates in Lebanese banks, whether in local or foreign currencies, and work to encourage and attract private foreign investments by creating an appropriate legal and economic environment, and moving away from for external loans as much as possible.